A Checklist of Avian Species in North Eastern Hill University Campus, Shillong, India - Patel, Nikita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
North Eastern Hill University Campus (25°36’36”N & 91°54’5’’E), Shillong, is having a very good biodiversity with various types of flora and fauna. This paper focuses on the avian diversity present in campus. The birds were observed and recorded at various locations of the campus. Seventy six species of birds belonging to 34 families and 8 orders were recorded from Nov 2019 to Sept 2022. There were 65 resident and 11 migratory birds. The present study is focused on preparing the checklist of birds with their occurrence, status as well as to create awareness for their conservation.